Low-temperature high-strength neutral soldering paste and manufacturing method thereof

By optimizing the raw material formula and process flow of solder paste, a low-temperature, high-strength neutral solder paste is produced, which solves the wettability and corrosion problems in stainless steel welding, achieves high-strength solder joints and environmentally friendly welding, and is suitable for precision welding scenarios.

CN120587749AActive Publication Date: 2025-09-05浙江强力控股有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511074117.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-01
Publication Date
2025-09-05
Estimated Expiration
2045-08-01

AI Technical Summary

Technical Problem

The existing technology has problems in stainless steel welding, such as poor wettability, poor welding quality, severe post-weld corrosion and high process complexity, especially when using traditional tin-silver-copper solder and strong acid flux.

Method used

Low-temperature, high-strength neutral solder paste is used. The raw material formula includes tin-based alloy powder, activator, enhancer and thixotropic agent. By optimizing the components and process flow, such as atomization powder making, vacuum stirring, homogenization and centrifugal degassing, the solder paste has good wettability and neutral properties.

Benefits of technology

It achieves low-temperature welding, improves the shear strength of solder joints, eliminates post-weld corrosion, reduces production costs, and is suitable for precision welding of robot charging terminals and smart home devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses low-temperature high-strength neutral soldering paste and a manufacturing method thereof.The soldering paste is prepared from, by weight, 87%-92% of tin-based alloy powder, 3.5%-5% of an activating agent, 0.5%-1.2% of a reinforcing agent, 0.5%-2% of a thixotropic agent and 2%-6% of a solvent; the tin-based alloy powder comprises the following alloy components in percentage by weight: 90%-95% of Sn, 2%-5% of Ag, 0.2%-1% of Cu and 2%-6% of Bi; the activating agent is formed by compounding dimethylolpropionic acid, sodium phosphate and ammonium fluoborate according to the weight ratio of 1: (0.1-0.4): (1.5-2); the reinforcing agent comprises reinforced aluminum oxide particles subjected to metallization treatment, and the particle size of the reinforced aluminum oxide particles is nanoscale. The soldering paste has the characteristics of being low in welding temperature, good in wettability, capable of improving the shearing strength of a welding spot, neutral, free of post-welding corrosion and the like, and is suitable for precise welding scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solder paste, and in particular to a low-temperature, high-strength neutral solder paste and a preparation method thereof. Background Art

[0002] With the development of new energy and high-power devices, stainless steel welding is being used in more and more scenarios. However, there are currently several problems with stainless steel welding: ① Traditional tin-silver-copper solder has poor wettability on the surface of stainless steel weldments (wetting angle > 55°) and requires reliance on strong acidic flux (such as hydrochloric acid flux), but this can lead to severe post-weld corrosion; ② The alloy layer of the brazed joint is discontinuous, which causes the Cr2O3 oxide layer on the surface of the stainless steel weldment to hinder the formation of the Fe-Sn alloy layer, thereby affecting the welding quality; ③ The currently available stainless steel solder paste or flux has strong post-weld corrosion, and post-weld cleaning must be performed to ensure that the solder joints do not continue to corrode, further increasing the complexity of the process and production costs.

[0003] In view of this, the present invention is proposed. Summary of the Invention

[0004] In order to overcome the above-mentioned defects, the present invention provides a low-temperature, high-strength neutral solder paste and a preparation method thereof. The preparation method is simple, reasonable and easy to operate, and the obtained solder paste has the characteristics of low welding temperature, good wettability, ability to improve solder joint shear strength, neutrality and no post-weld corrosion. It can be well applied to precision welding scenarios such as robot charging terminals and smart home devices.

[0005] The technical solution adopted by the present invention to solve the technical problem is: a low-temperature, high-strength neutral solder paste, which has the following raw material formula, calculated by weight percentage: 87% to 92% tin-based alloy powder, 3.5% to 5% activator, 0.5% to 1.2% reinforcing agent, 0.5% to 2% thixotropic agent, and 2% to 6% solvent; Wherein, based on the total weight of the tin-based alloy powder, the alloy components and their weight percentages in the tin-based alloy powder are: Sn 90% to 95%, Ag 2% to 5%, Cu 0.2% to 1% and Bi 2% to 6%; The activator is composed of dihydroxymethylpropionic acid, sodium phosphate and ammonium fluoroborate in a weight ratio of 1: (0.1-0.4): (1.5-2); the reinforcing agent includes metallized reinforced alumina particles, and the particle size of the reinforced alumina particles is nanometer level.

[0006] As a further improvement of the present invention, based on the total weight of the tin-based alloy powder and calculated by weight percentage, the tin-based alloy powder is composed of 92.5% Sn, 3% Ag, 0.5% Cu and 4% Bi.

[0007] As a further improvement of the present invention, the particle size of the tin-based alloy powder is 15 to 25 μm, and the oxygen content is not greater than 200 ppm.

[0008] As a further improvement of the present invention, the enhanced alumina particles are composed of alumina particles and a nickel layer plated on the surface of the alumina particles, and the particle size of the enhanced alumina particles is 10 to 30 nm.

[0009] As a further improvement of the present invention, the reinforcing agent further includes a silane coupling agent, and the weight ratio of the reinforcing alumina particles to the silane coupling agent is 1:(0.2-0.5).

[0010] As a further improvement of the present invention, the thixotropic agent is modified fatty acid amide, the solvent is methyl glycolate, and the weight ratio of the thixotropic agent to the solvent is 1:(2-5).

[0011] The present invention also provides a method for preparing low-temperature, high-strength neutral solder paste, comprising the following steps: S1: A tin-based alloy powder having a particle size of 15 to 25 μm and an oxygen content of no more than 200 ppm is prepared by an atomization powder making process; S2: After stirring and mixing the formulated amount of thixotropic agent and solvent, adding the formulated amount of dimethylolpropionic acid, sodium phosphate and ammonium fluoroborate thereto, and stirring and mixing again to obtain a first mixture; S3: adding the formulated amount of reinforcing agent to the obtained first mixture after soaking, and stirring thoroughly until the reinforcing agent is evenly dispersed to obtain a second mixture; S4: Put the formulated amount of tin-based alloy powder and the obtained second mixture into a planetary mixer and stir at a vacuum degree of 10 2 Pa~10 -1 The low-temperature, high-strength neutral solder paste is prepared by stirring for 30 to 50 minutes at a stirring speed of 50 to 60 rpm.

[0012] As a further improvement of the present invention, the method further comprises S5: sequentially homogenizing and centrifuging the obtained low-temperature, high-strength, neutral solder paste to obtain a finished product of the low-temperature, high-strength, neutral solder paste.

[0013] As a further improvement of the present invention, in the above S5, the obtained low-temperature, high-strength, neutral solder paste is subjected to a three-roller process three times to control the viscosity of the low-temperature, high-strength, neutral solder paste to be 180±20 Pa·s.

[0014] As a further improvement of the present invention, in the above S5, the low-temperature, high-strength, neutral solder paste after homogenization is transferred to a centrifugal degassing machine and degassed at a rotation speed of 1000-1500 rpm for 3-5 minutes to obtain the finished product of the low-temperature, high-strength, neutral solder paste.

[0015] The beneficial effects of the present invention are as follows: ① Through technological innovation, the present invention produces a solder paste with low soldering temperature, good wettability, enhanced solder joint shear strength, neutrality, and no post-solder corrosion. This solder paste is well suited for precision soldering applications such as robot charging terminals and smart home devices, and can reduce costs by over 60%. ② The solder paste production method provided by the present invention is simple, reasonable, and easy to operate, and the relevant raw materials are readily available, inexpensive, and more environmentally friendly. DETAILED DESCRIPTION

[0016] The present invention will be further described in detail below with reference to specific examples, but the present invention is not limited to these examples.

[0017] This application discloses a low-temperature, high-strength neutral solder paste and its production method. This production method is simple, reasonable, and easy to operate. The resulting solder paste has the characteristics of low welding temperature, good wettability, improved solder joint shear strength, neutrality, and no post-weld corrosion. It is well suited for precision welding scenarios such as robot charging terminals and smart home devices. The main reason for this achievement is that this application optimizes and innovates the raw material formula of the solder paste. The details are as follows: 1. Prepare the low-temperature, high-strength, neutral solder paste described in this application;

[0018] Example 1:

[0019] This embodiment 1 provides a method for preparing a low-temperature, high-strength, neutral solder paste, which mainly includes the following steps: S1: A tin-based alloy powder having a particle size of 15 to 25 μm and an oxygen content of no more than 200 ppm is prepared by an atomization powder making process.

[0020] Specifically, the specific method for preparing the tin-based alloy powder used in this embodiment is as follows: S11: Based on the weight percentage, a Sn-Ag-Cu-Bi alloy composed of 92.5% Sn, 3% Ag, 0.5% Cu and 4% Bi was prepared under a vacuum of 10 5 Pa~10 2 The alloy melt is obtained by melting under the conditions of Pa and a melting temperature of 850°C; S12: Processing the resulting alloy melt into a tin-based alloy powder having a particle size of 15 to 25 μm (preferably 20 μm ± 2 μm) and an oxygen content of no more than 200 ppm by an atomization powdering process. It is understood that based on the composition of the Sn-Ag-Cu-Bi alloy, the chemical formula of the tin-based alloy powder can be written as Sn92.5Ag3Cu0.5Bi4.

[0021] S2: After stirring and mixing 1 kg of modified fatty acid amide and 4 kg of methyl glycolate at 75° C. to 80° C., 1.4 kg of dimethylolpropionic acid, 0.28 kg of sodium phosphate and 2.52 kg of ammonium fluoroborate were added thereto, and the mixture was stirred and mixed again to obtain a first mixture; S3: 0.625 kg of reinforced alumina particles and 0.225 kg of silane coupling agent (KH-550) were mixed and soaked, and then added to the obtained first mixture, and stirred thoroughly until the reinforcing agent was evenly dispersed to obtain a second mixture; Note: The enhanced alumina particles are composed of alumina particles and a nickel layer plated on the surface of the alumina particles. Therefore, the chemical expression of the enhanced alumina particles can be written as Ni@Al2O3; in addition, the particle size of the enhanced alumina particles is optimally controlled to be 10 to 30 nm (more preferably 20 nm).

[0022] S4: 89.95 kg of tin-based alloy powder (Sn92.5Ag3Cu0.5Bi4) and the obtained second mixture were put into a planetary mixer and the vacuum degree was 10 2 Pa~10 -1 Pa and stirring at a speed of 50 to 60 rpm for 30 to 50 minutes to obtain the low-temperature, high-strength neutral solder paste.

[0023] Furthermore, in this embodiment, the stirring speed is preferably 50 rpm and the stirring time is 40 min.

[0024] S5: performing homogenization and centrifugal degassing treatments on the obtained low-temperature high-strength neutral solder paste in sequence to obtain a finished product of the low-temperature high-strength neutral solder paste.

[0025] The homogenization method is as follows: the obtained low-temperature, high-strength, neutral solder paste is passed through a three-roller machine three times, and the gap between the rollers in the three-roller machine is controlled to be ≤10 μm, so that the viscosity of the low-temperature, high-strength, neutral solder paste is controlled to be 180±20 Pa·s.

[0026] The centrifugal degassing treatment method is as follows: the low-temperature, high-strength, neutral solder paste after homogenization is filled and packaged, and then transferred to a centrifugal degassing machine, and degassed at a speed of 1000-1500 rpm for 3-5 minutes to obtain the finished product of the low-temperature, high-strength, neutral solder paste.

[0027] Furthermore, in this embodiment, the rotation speed is preferably 1500 rpm and the degassing time is 3 minutes.

[0028] Example 2:

[0029] This embodiment 2 also provides a method for preparing a low-temperature, high-strength neutral solder paste. Compared with embodiment 1, this embodiment 2 is different in that the raw material formula of the solder paste used in this embodiment 2 is different from that in embodiment 1.

[0030] Specifically, the solder paste raw material formula used in this Example 2 is: 1.75 kg of modified fatty acid amide, 5.25 kg of methyl glycolate, 1.5 kg of dimethylolpropionic acid, 0.6 kg of sodium phosphate, 2.4 kg of ammonium fluoroborate, 0.7 kg of reinforced alumina particles, 0.35 kg of silane coupling agent (KH-550), and 87.45 kg of tin-based alloy powder (Sn92.5Ag3Cu0.5Bi4).

[0031] Note: In addition to the above differences, the specific processing methods and processing parameters used in each step of this embodiment 2, such as melting parameters, stirring and mixing parameters, homogenization parameters, centrifugal degassing parameters, etc., are the same as those in embodiment 1, so they are not repeated here.

[0032] Example 3:

[0033] This embodiment 3 also provides a method for preparing a low-temperature, high-strength neutral solder paste. Compared with embodiment 1, this embodiment 3 is different in that the raw material formula of the solder paste used in this embodiment 3 is different from that in embodiment 1.

[0034] Specifically, the solder paste raw material formula used in this Example 3 is: 1 kg of modified fatty acid amide, 3 kg of methyl glycolate, 1.2 kg of dimethylolpropionic acid, 0.24 kg of sodium phosphate, 2.16 kg of ammonium fluoroborate, 0.4 kg of reinforced alumina particles, 0.2 kg of silane coupling agent (KH-550), and 91.8 kg of tin-based alloy powder (Sn91.3Ag4Cu0.7Bi4).

[0035] Note: ① Apart from the above differences, the specific processing methods and parameters used in each step of Example 3, such as melting parameters, stirring and mixing parameters, homogenization parameters, and centrifugal degassing parameters, are the same as those in Example 1 and are therefore not described here. ② It will be understood that, by weight percentage, the tin-based alloy powder used in Example 3 is composed of 91.3% Sn, 4% Ag, 0.7% Cu, and 4% Bi.

[0036] 2. Conducting performance tests on the solder paste prepared in this application; The solder pastes prepared in Examples 1 to 3 of the present application and a conventional chlorine-containing stainless steel solder paste (comparative example) were tested for performance. The test method was as follows: Step 1) Clean a 20mm×20mm×1mm 304 stainless steel sheet and an 8mm×8mm T2 copper plate with isopropyl alcohol.

[0037] Step 2) Print the solder pastes prepared in Examples 1 to 3 of the present application and the conventional chlorine-containing stainless steel solder paste on a 304 stainless steel sheet, respectively, and the printing thickness of the above four solder pastes is 0.15 mm. Then, a T2 copper plate is attached to the printed solder paste.

[0038] Step 3) Place the prepared parts to be welded (i.e., a combination of 304 stainless steel sheet and T2 copper plate) into a reflow furnace protected by a nitrogen atmosphere (oxygen content less than 100ppm) for welding. The reflow chain speed is set to 1.2m / min, the heating rate is set to 2℃ / s, the peak temperature of the welding zone is set to 250℃, and the welding time is set to about 35s.

[0039] Step 4) After welding is completed, the weldment is subjected to wetting angle test, resistivity test, shear strength test, thermal conductivity test, salt spray test, copper mirror test and ion contamination test, etc.; among them, the wetting angle test is carried out in accordance with the test standard JIS Z 3197; the resistivity test is carried out in accordance with the test standard ASTM B193 (four-probe method); the shear strength test is carried out in accordance with the test standard GB / T 11363; the salt spray test is carried out in accordance with the test standard GB / T2423.17-2024; the thermal conductivity test is carried out in accordance with the LFA 467 laser flash method; the copper mirror test is carried out in accordance with IPC TM-650 2.3.32; and the ion contamination test is carried out in accordance with IPC TM-650 2.3.28.

[0040] Table 1 below shows the performance test results of the solder pastes prepared in Examples 1 to 3 of the present application and a traditional chlorine-containing stainless steel solder paste.

[0041] Table 1 Performance test results of the solder pastes obtained in Examples 1 to 3 of the present application and conventional chlorine-containing stainless steel solder pastes Table 1 shows that: ① When soldering with the solder paste prepared in this application, a wetting angle of 16° to 18° is achieved, which is significantly smaller than the 52° wetting angle achieved with conventional chlorine-containing stainless steel solder paste. This indicates that the solder paste prepared in this application has excellent wettability on the stainless steel weldment, resulting in a tight bond. ② When soldering with the solder paste prepared in this application, a shear strength of 25 to 28 MPa is achieved at the solder joint, which is twice the shear strength of 14 MPa achieved with conventional chlorine-containing stainless steel solder paste. This indicates that the solder paste prepared in this application forms a high-strength solder joint alloy layer (IMC layer). ③ When soldering with the solder paste prepared in this application, the resistivity of the solder joint does not exceed 13 μΩ·cm, and the thermal conductivity is greater than 69 W / mk, both exceeding the resistivity and thermal conductivity of the solder joint achieved with conventional chlorine-containing stainless steel solder paste. This indicates that the solder paste prepared in this application forms a good metallurgical bond with the stainless steel weldment, resulting in excellent weld quality. ④ When using the solder paste prepared in this application for welding, the stainless steel weldment can be free of corrosion and penetration after welding, which is far better than the situation after welding of traditional chlorine-containing stainless steel solder paste. ⑤ When using the solder paste prepared in this application for welding, the ion contamination is very low (the highest is only 1.03μg / cm 2 ), which is much lower than the ion contamination level produced by traditional chlorine-containing stainless steel solder paste (5.6μg / cm 2 ); This indicates that the cleanliness of the solder joints and the soldering environment is extremely high when soldering is performed using the solder paste obtained in this application.

[0042] The reason why the solder paste obtained in the present application can achieve the above advantages is mainly due to the optimization and innovation of the raw material formula of the solder paste in the present application, which is specifically manifested in: ① When preparing the solder paste, the present application selects a tin-based alloy powder composed of four metal elements, Sn, Ag, Cu and Bi, compounded according to a specific formula. Among them, the Bi element can not only lower the melting point of the solder paste (measured by DSC, the melting point of the solder paste obtained in the present application is 217°C, which can achieve reliable welding of stainless steel materials with copper materials and other materials at 250°C), but also suppress the brittleness of Cu6Sn5, thereby making the solder joint alloy layer (IMC layer) have a certain toughness; the Ag element can improve the wettability of the solder paste, thereby ensuring the continuity of the solder joint alloy layer (IMC layer). ② When formulating the solder paste, this application uses an activator composed of dimethylolpropionic acid, sodium phosphate, and ammonium fluoborate in a specific weight ratio. Ammonium fluoborate selectively corrodes the surface oxides of stainless steel, effectively removing the oxide layer and improving the wettability of the solder paste. Sodium phosphate forms a temporary protective film to reduce post-weld corrosion. Furthermore, the combination of sodium phosphate and ammonium fluoborate neutralizes the acidic byproducts produced by ammonium fluoborate corrosion, preventing localized excessive corrosion. Dimethylolpropionic acid assists ammonium fluoborate in accelerating the dissolution of oxides on the stainless steel surface, further improving the wettability of the solder paste. ③ When formulating the solder paste, this application uses metallized reinforced alumina particles as a reinforcing agent, significantly increasing the density of the solder joint alloy layer (IMC layer) and, consequently, the shear strength of the solder joint. Furthermore, the tin coating on the reinforced alumina particles also facilitates stress transfer, improves thermal conductivity, reduces soldering temperature, maintains solder paste fluidity, and enhances the bonding between the alumina particles and other components. ④ When preparing the solder paste, this application optimizes and controls each component so that the solder paste is neutral as a whole (pH value is 6.5-7.1), ensuring that the post-soldering residue is close to neutral and can pass the 48-hour salt spray corrosion test and copper mirror test. In addition, the post-soldering residue can be exempted from cleaning, which is environmentally friendly and reduces costs.

[0043] In addition, in addition to the above-mentioned optimization and innovation of the raw material formula of the solder paste, this application also adopts an optimal process combination, especially the atomization powder making, vacuum stirring, homogenization, centrifugal degassing and other processes, which can well ensure the uniform texture and excellent performance of the solder paste.

[0044] In summary, through technological innovation, this application has produced a solder paste with the characteristics of low welding temperature, good wettability, ability to improve solder joint shear strength, neutrality and no post-weld corrosion. It can be well applied to precision welding scenarios such as robot charging terminals and smart home devices, and can reduce costs by more than 60%.

[0045] In the above description, many specific details are set forth in order to fully understand the present invention. However, the above description is only a preferred embodiment of the present invention. The present invention can be implemented in many other ways different from those described herein, so the present invention is not limited to the specific implementation disclosed above. At the same time, any person skilled in the art can make many possible changes and modifications to the technical solution of the present invention using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.

Claims

1. A low-temperature, high-strength, neutral solder paste, characterized by: The raw material formula is as follows, calculated by weight percentage: 87% to 92% of tin-based alloy powder, 3.5% to 5% of activator, 0.5% to 1.2% of reinforcing agent, 0.5% to 2% of thixotropic agent, and 2% to 6% of solvent; Wherein, based on the total weight of the tin-based alloy powder, the alloy components and their weight percentages in the tin-based alloy powder are: Sn 90% to 95%, Ag 2% to 5%, Cu 0.2% to 1% and Bi 2% to 6%; The activator is composed of dihydroxymethylpropionic acid, sodium phosphate and ammonium fluoroborate in a weight ratio of 1: (0.1-0.4): (1.5-2); the reinforcing agent includes metallized reinforced alumina particles, and the particle size of the reinforced alumina particles is nanometer level.

2. The low-temperature, high-strength, neutral solder paste according to claim 1, characterized in that: Based on the total weight of the tin-based alloy powder and calculated by weight percentage, the tin-based alloy powder is composed of 92.5% Sn, 3% Ag, 0.5% Cu and 4% Bi.

3. The low-temperature, high-strength, neutral solder paste according to claim 1, characterized in that: The particle size of the tin-based alloy powder is 15 to 25 μm, and the oxygen content is no more than 200 ppm.

4. The low-temperature, high-strength, neutral solder paste according to claim 1, characterized in that: The enhanced alumina particles consist of alumina particles and a nickel layer plated on the surface of the alumina particles, and the particle size of the enhanced alumina particles is 10-30 nm.

5. The low-temperature, high-strength, neutral solder paste according to claim 1, characterized in that: The reinforcing agent further includes a silane coupling agent, and the weight ratio of the reinforcing alumina particles to the silane coupling agent is 1:(0.2-0.5).

6. The low-temperature, high-strength, neutral solder paste according to claim 1, characterized in that: The thixotropic agent is modified fatty acid amide, the solvent is methyl glycolate, and the weight ratio of the thixotropic agent to the solvent is 1:(2-5).

7. A method for preparing a low-temperature, high-strength, neutral solder paste according to any one of claims 1 to 6, characterized in that: The production steps include: S1: A tin-based alloy powder having a particle size of 15 to 25 μm and an oxygen content of no more than 200 ppm is prepared by an atomization powder making process; S2: After stirring and mixing the formulated amount of thixotropic agent and solvent, adding the formulated amount of dimethylolpropionic acid, sodium phosphate and ammonium fluoroborate thereto, and stirring and mixing again to obtain a first mixture; S3: adding the formulated amount of reinforcing agent to the obtained first mixture after soaking, and stirring thoroughly until the reinforcing agent is evenly dispersed to obtain a second mixture; S4: Put the formulated amount of tin-based alloy powder and the obtained second mixture into a planetary mixer and stir at a vacuum degree of 10 2 Pa~10 -1 The low-temperature, high-strength neutral solder paste is prepared by stirring for 30 to 50 minutes at a stirring speed of 50 to 60 rpm.

8. The method for preparing the low-temperature, high-strength, neutral solder paste according to claim 7, wherein: The method further includes S5: sequentially performing homogenization and centrifugal degassing treatments on the obtained low-temperature high-strength neutral solder paste to obtain a finished product of the low-temperature high-strength neutral solder paste.

9. The method for preparing the low-temperature, high-strength, neutral solder paste according to claim 8, wherein: In the above S5, the obtained low-temperature, high-strength, neutral solder paste is subjected to a three-roller process three times, so that the viscosity of the low-temperature, high-strength, neutral solder paste is controlled to be 180±20 Pa·s.

10. The method for preparing low-temperature, high-strength, neutral solder paste according to claim 8, characterized in that: In the above S5, the low-temperature, high-strength, neutral solder paste after homogenization is transferred to a centrifugal degassing machine and degassed at a rotation speed of 1000-1500 rpm for 3-5 minutes to obtain the finished product of the low-temperature, high-strength, neutral solder paste.

Citation Information

Patent Citations

  • Low-temperature environment-friendly multi-element alloy solder paste and preparation method thereof

    CN111590241A

  • A water-soluble die-bonding solder paste for high-power LED packaging and its preparation method

    CN114932335A

  • Low-melting-point soldering paste capable of welding aluminum material

    CN115229379A

  • Water-based flux paste, manufacturing method thereof and water-based soldering paste

    CN117697232A